Evaluasi Implementasi Pembelajaran Berdiferensiasi di Sekolah Penggerak PAUD Kabupaten Pringsewu (Studi evaluasi PAUD formal sekolah penggerak ) - Siti Rodiyah; Siswoyo; Fatqul Hajar Aswad (Manajemen Pendidikan, 2024)
This study evaluates the implementation of differentiated learning in PAUD driving schools in Pringsewu Regency using the CIPP (Context, Input, Process, Product) evaluation model. The background of the research is that the application of differentiated learning in local PAUD institutions has not been evenly distributed. The research method uses a descriptive qualitative approach with interview, documentation, and observation instruments. The results of the study show that the implementation of differentiated learning has been effective, as seen from the suitability of the school environment and children's characteristics. Input factors include relevant curriculum, resources, and learning materials. The learning process uses various strategies according to students' readiness, interests, and learning profiles. Student learning outcomes include improved material comprehension, critical thinking skills, motivation, confidence, and active participation. The research recommends teacher competency training, the formation of learning communities, and periodic monitoring and evaluation. The implication is the need for curriculum adjustments and the commitment of all stakeholders to create a meaningful learning environment and support differentiated learning.